the Sustainable development of two geographical regions in Slovenia: repercussions for tourism: Case study of the Posavje and Dolenjska regions - Veljković, Božidar; Ogorelc, Marko; Pavić, Lazar; Koščak, Marko (Turizam, 2023)
The opportunities of participatory democratic communication in the process of innovative, sustainable and socially responsible tourism development policy creation have never been sufficiently exploited due to constant changes in this area of ​​social communication. In this sense, scientific and technical progress in the development of information and communication technology (ICT) allowed for an unprecedented level of media convergent communication, thus offering tourist destinations new opportunities to conceptualize communication functions through the institutionalization of the Destination Management Organization (DMO). Communication management has surely a highly significant role in terms of overall tourist destination management and balanced communication with the relating groups of the public, as well as maintaining communication processes within that destination’s organisational structure. In this study, based on theoretical and empirical research and case studies, we offer a concept of a communication model, which enables democratic participatory communication in an optimal, regional tourist destination. This is the Posavje and Dolenjska geographic regions of Slovenia, in which each municipality have their own municipal tourism development strategies, but do not have a common regional strategy that best coincides with the parameters determining the optimal tourist destination (problem). Based on the research, we offer solutions to this tourism development issue in the form of new conceptualization of communication functions in these tourist destinations.
Keywords: communication, destination management organisation, participatory communication, sustainable development, tourism